PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERATING (Studi Empiris pada Perusahaan Manufaktur Sektor Property dan Real Estate yang terdaftar di Bursa Efek Indonesia Tahun 2011 – 2015 ) - Apriyani, Yensi Febya; Sutjahyani, Dewi (Universitas 17 Agustus 1945 Surabaya, 2018)
ABSTRACT The purpose of this research is to analyze (1) The influence of CorporateSocial Responsibility (CSR) to firm value. (2) Profitability moderatinginfluence on the relationship of Corporate Social Responsibility (CSR) to firmvalue. The population used in this research is a manufacturing company sectorproperty and real estate sector listed in Indonesia Stock Exchange (IDX) years2011-2015. The sample was 11 companies using purposive samplingmethod.Data analysis techniques include (1) Descriptive Statistics (2) ClassicAssumption Test: Normality, Multikolinierity, Heteroskedastisity andAutocorrelation (3) Multiple Linear Regression Analysis (4) Goodness of FitTest : (a) The Coefficient of Determination (b) Statistic Test F (5) Hypothesistest using Test Statistic t. The results of this research showed that (1)Corporate Social Responsibility (CSR) influence negative and significant tofirm value. (2) Profitability in this research is proxied by Net Profit Margin(NPM), Return on Assets (ROA) and Return On Equity (ROE) : (a)Profitability is proxied by Net Profit Margin (NPM) able to moderate theinfluence of relationship Corporate Social Responsibility (CSR) to corporatevalue is profitability weaken the influence of relationship Corporate SocialResponsibility (CSR) to firm value (b) Profitability is proxied by Return onAssets (ROA) was not able to moderate the influence of relationshipCorporate Social Responsibility (CSR) to firm value (c) Profitability isproxied by Return On Equity (ROE) was not able to moderate the influenceof relationship Corporate Social Responsibility (CSR) to firm value.Keywords : Corporate Social Responsibility, Profitability, Firm Value